Compatibility of the entomopathogenic fungus Beauveria bassiana with tritlumuron - VÁSQUEZ-P., CARMEN A.; SALDARRAGA-O., YAMILLÉ; PINEDA-G.J, FABIO (Revista Colombiana de Entomología, 2004)
The combined use of chemical and biological insecticides presents a promising and rational alternative to control insect pests of agricultura! and medica! importance. The compatibilities of the lnra297, Cenicafé.Bb9205 and UdeA , strains of the fungus B. bassiana with the insecticide Starycide S.C. 480 Bayer" (trlflumuron). a chitin synthesis inhibitor in insects, were evaluated. Combinations of three concentrations of each strain of B. bassiana (3x105, 1x107 and 3x108 conidios/ml) and triflumuron (0,05 0,025 and 0,0125 µ,g/¡.d) were tested. The fungus suspension was used as a control. The compatibility of the two agents was evaluated based on conidial germination in a solid medium (Sabouraud dextrose agar) and mycelial growth in a liquid medium. Conidial germination was observed at 24 and 48 h and mycelial growth at 7 days. The germinated and non-germinated conidia and dry mycelium weight were the variables used in statistical analysis. The presence of triflumuron inhibited neither conidial germination nor mycelial growth of B. bassiana, demonstrating the compatibility. However, both conidial germination and mycelial growth in the presence of triflumuron varied among the three fungal strains that were evaluated.